Costing of IPL players depends on performance - An exemplary for Multi - Criteria Decision Making Procedure - Nagendra, Kolluri Venkata; Mallipudi, Prasannaraj (International Journal of Psychosocial Rehabilitation, 2020)
Cricket is a global sport played around in 100 countries. The game players should be the best performers with the best in physical fitness and should be without any injury. As cricket is fond of many viewers in all countries, hence a new norm IPL has been introduced in 2008. IPL the Indian Premier League is the latest Twenty20 Cricket League which has been practicing for the past three years i.e, 2008. The IPL varies from the regular norms which are been followed in the regular Cricket World. The team owners could select the talented players for their team by following the auction process. Maximum 4 foreign players would be allotted for each and every IPL cricket team. Though the overall wage cap For the IPL cricket players is about 5 Millions, the organization has to spend a minimum of 3.3 millions on the players depending on the amount of salary allotted salary cap. This paper aims to inquire the extent to which the player costings based on their performances. IPL and Cricket are being the favourite sports of many, because of huge following to these global sport there are many systems been proposed to make decisions. The outcomes or the results can also be assured by going for the comparative analysis with the dataset prescribed here (K-NN, SVM, Linear Regression), compare the results with respect to these algorithms. Among these algorithms, our algorithms give the outcomes with the highest accuracy. Our proposed system will give you more desirable results than the present existing systems.